2003
DOI: 10.1007/s00234-002-0934-4
|View full text |Cite
|
Sign up to set email alerts
|

Internal carotid artery aneurysms, cranial nerve dysfunction and headache: the role of deformation and pulsation

Abstract: Cranial nerve dysfunction and headache may occur with unruptured aneurysms of the cavernous and supraclinoid portions of the internal carotid artery. Nerve deformation (mass effect) and transmitted pulsations have been suggested as pathogenetic mechanisms. Differentiation may be possible by studying effects of endovascular treatment with Guglielmi detachable coils. Symptoms and signs of cranial neuropathy were retrospectively contrasted with angiographic aneurysm volumes before and after treatment in 10 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 5 publications
1
16
0
1
Order By: Relevance
“…Reports are mainly highly selected retrospective case series of aneurysms at specific locations-usually representing symptomatic large and giant aneurysms (5,24). The proportion of "complete resolution" of oculomotor nerve palsies may be based on retrospective record review or subjective questionnaires without neuro-ophthalmic examination (16,20,31).…”
Section: Introductionmentioning
confidence: 99%
“…Reports are mainly highly selected retrospective case series of aneurysms at specific locations-usually representing symptomatic large and giant aneurysms (5,24). The proportion of "complete resolution" of oculomotor nerve palsies may be based on retrospective record review or subjective questionnaires without neuro-ophthalmic examination (16,20,31).…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Possible mechanisms of improvement of cranial neuropathy with treatment of aneurysms include reduction of direct mass effect upon the nerve, reduction of the inflammatory process causing neuropathy, and diminution of the pulsations causing a waterhammer effect upon the nerve. [2][3][4]7,8,17 Advocates of surgical decompression argue that aneurysm embolization with coils or liquid embolic agents cannot provide mechanical decompression of the injured nerve and is therefore an inferior option. 18 However, a water-hammer effect of arterial pulsation appears to be a factor in cranial nerve dysfunction in this setting, and can be reduced with embolization of the aneurysm.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of this headache remains elusive. Possible pathogenetic mechanisms include mass effect (caused by gradual or sudden growth of an aneurysm), intramural dissection within the aneurysmal wall and transmitted pulsations [6,7]. To investigate the principal pathophysiological mechanism, Rodriguez-Catarino and colleagues retrospectively studied 10 cases of patients with unruptured symptomatic aneurysms treated by the endovascular route and found that other than the consistent increase in aneurysm volume after embolisation, no clinical deterioration was observed, thus concluding that mass effect may play a minor role in symptomatology of unruptured aneurysms and that transmitted pulsations may be more important [7].…”
Section: Discussionmentioning
confidence: 99%